Malacofauna of lotic environments in the Northeast and Brazilian semiarid region: current knowledge and new records - LEAL,MANUELLA F. (2021)
Abstract Despite the great diversity, economic and environmental importance of limnic mollusks, the group is still little investigated in the Brazilian semiarid region, especially in the state of Piauí. Thus, this work aims to gather information on the diversity of limnic mollusks in the Brazilian Northeast and the semiarid region, including new records for the state of Piauí, northeastern Brazil. For this, collections in the urban perimeter of the Itaim and Guaribas Rivers, municipalities of Itainópolis, and Picos, respectively, between October 2017 and September 2019. Besides, a literature review was conducted on studies of malacofauna in the Northeast and the Brazilian semiarid region. A total of 11 species from the classes Gastropoda and Bivalvia were collected on the rivers of Piauí, being the first record of Uncancylus concentricus for the Northeast region. For lotic environments in the state of Piauí, Drepanotrema schubarti, Pomacea canaliculata, Pisidium dorbignyi and Stenophysa marmorata were registered for the first time. Then, it was possible to verify that the Northeast of Brazil has 71 species registered, of which 34 occur in the semiarid. The diversity of species surveyed and the first record of the occurrence of several of them for the semiarid region demonstrate the importance of expanding studies involving this group to other areas. The present study is the first to gather and increase the information available on the fauna of limnic mollusks for the Northeast and Brazilian semiarid regions. The information gathered here may contribute to future research and to the species conservation and the environments they occupy, especially considering the presence of non- native and vector species.